Surgical Treatment of Picevodogasteric Bleeding in Patients with Liver Cirrhosis - Atanazar, Niyazmetov (PT. Antis International Publisher, 2024)
A little more than half a century has passed since the fundamental ideas about the morphological types of such liver lesions as hepatitis, hepatosis, cirrhosis were formed (Bluger A.F., Novitsky I.N., 1984), Subsequent morphological studies have established that LC- it is the result of a pathological reconstruction of the lobular structure of the organ. From a clinical point of view, cirrhosis can be defined as a progressive (or slowly progressive) diffuse chronic polyetiologic liver disease. This is the final stage of adversely occurring forms of chronic hepatitis, due to obstruction of the outflow of bile or blood from the liver or genetically determined metabolic defects. The disease is characterized by a significant decrease in the mass of functioning liver cells, a pronounced fibrosing reaction, a restructuring of the parenchyma and the vasculature of the liver (Loginov A.S., 1987).